2015
DOI: 10.1073/pnas.1503436112
|View full text |Cite
|
Sign up to set email alerts
|

Stable long-range interhemispheric coordination is supported by direct anatomical projections

Abstract: The functional interaction between the brain's two hemispheres includes a unique set of connections between corresponding regions in opposite hemispheres (i.e., homotopic regions) that are consistently reported to be exceptionally strong compared with other interhemispheric (i.e., heterotopic) connections. The strength of homotopic functional connectivity (FC) is thought to be mediated by the regions' shared functional roles and their structural connectivity. Recently, homotopic FC was reported to be stable ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
97
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(111 citation statements)
references
References 60 publications
14
97
0
Order By: Relevance
“…The parabrachial nucleus is one source of neurotensinergic projections to the VTA (48) and projects bilaterally to midbrain dopamine neurons (49). Regardless of the mechanism, the synchronicity in dopamine release between hemispheres uncovered here establishes that chemical signaling, like physiological activity (50), is tightly coupled across the brain. Given that amphetamine-induced dopamine transients remained in the unilaterally lesioned animals, it is apparent that interhemispherical connectivity contributes to psychostimulant-induced dopamine fluctuations.…”
Section: Discussionmentioning
confidence: 84%
“…The parabrachial nucleus is one source of neurotensinergic projections to the VTA (48) and projects bilaterally to midbrain dopamine neurons (49). Regardless of the mechanism, the synchronicity in dopamine release between hemispheres uncovered here establishes that chemical signaling, like physiological activity (50), is tightly coupled across the brain. Given that amphetamine-induced dopamine transients remained in the unilaterally lesioned animals, it is apparent that interhemispherical connectivity contributes to psychostimulant-induced dopamine fluctuations.…”
Section: Discussionmentioning
confidence: 84%
“…Homotopic FC is more stable across time and across conditions than other types of functional connections (54). It is possible that our FC-deficit models load most heavily on interhemispheric FC because this stability enables greater fidelity in measurement of disruption.…”
Section: Structure Vs Function-relative Contribution To Different Bementioning
confidence: 97%
“…Positive correlation has been found between functional connectivity and structural connectivity within local areas in somatosensory cortex (Wang et al, 2013). Other studies, investigating the whole brain connections including longdistance ROIs, found that brain regions with direct structural connections also exhibited stable functional connectivity (Shen et al, 2012(Shen et al, , 2015. A lesion study in monkeys further showed that interhemispheric functional connectivity was severely reduced with resection of interhemispheric fiber connections.…”
Section: Structural-functional Relationship In Animal Studiesmentioning
confidence: 99%
“…Similarities between macaque brain networks and human brain networks have been suggested (Margulies et al, 2009;Mars et al, 2011;Shen et al, 2015). In macaques, whereas functional connectivity, quantified by cross correlation, was sometimes derived from fMRI data (Adachi et al, 2012;Deco et al, 2014;Margulies et al, 2009;Mars et al, 2011;Shen et al, 2012Shen et al, , 2015, structural connectivity was often based on tract tracing techniques, which are not possible in humans. The tracer molecules injected into the source brain region are absorbed and transported by axons to target brain regions, resulting in a tracer density map.…”
Section: Structural-functional Relationship In Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation